Do disabilities impede the use of information and communication technologies? Findings of a repeated cross-sectional study - 2003-2015 - Sabina Lissitsa; Galit Madar (BMC, 2018)
Abstract Background The current research focuses on trends of Internet adoption and digital uses among people with disabilities over a thirteen-year period. Methods The study is based on data elicited from a repeated cross-sectional study collected by means of Annual Social Surveys conducted by Israel's Central Bureau of Statistics between 2003 and 2015. The sample included 95,145 respondents, among them 22,290 respondents with disabilities. Results The rate of Internet access and digital uses increased continuously among disabled people; however the gap between them and the population without disabilities was preserved. We found that Internet use depends on a number of socio-economic characteristic. Socio-demographic variables were much more powerful in predicting Internet use vs non-use among the total population, compared to predicting digital uses among Internet users. Conclusions Our findings make it possible to identify disadvantaged groups in which disability intersects with low rates of Internet adoption and belonging to unprivileged groups: Arabs, the religious, the elderly, lower SES individuals. The effects of most of these variables did not change in the period under study. Generally, we recommend finding a way to promote courses that focus on promoting digital literacy in general and eHealth literacy in particular in small groups of people of similar age, digital skill level and motor / health problems. Considering the high representation of Arabs among people with disabilities and lower rates of Internet adoption and use among Arabs, it is recommended that efforts continue to increase the scope and quality of Arabic language content published on Israeli eHealth sites. In order to diminish income-based digital divide we recommend providing publicly accessible free information technologies, for example, in community clubs, senior citizen clubs, and independent- and assisted- living projects for the disabled.